Insights into the mechanism of electrocatalysis of the oxygen reduction reaction by a porphyrinic metal organic framework. Issue 48 (1st June 2017) - Lions, M.; Tommasino, J.-B.; Chattot, R.; Abeykoon, B.; Guillou, N.; Devic, T.; Demessence, A.; Cardenas, L.; Maillard, F.; Fateeva, A.
Abstract : Insights into the mechanism of electrocatalysis of the oxygen reduction reaction by a porphyrinic metal organic framework. Abstract : Metal Organic Frameworks (MOFs) have been recently proposed as promising electrocatalysts, yet the exact nature of the mechanisms in play has not been addressed in depth. By comparing the electrocatalytic activity of a MOF for the oxygen reduction reaction (ORR) and the corresponding molecular building units through electrochemical techniques, here, we investigate the nature of the catalytic sites, their redox states and the electron transfer pathways.